PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS COMPUTER ASSISTED INSTRUCTION (CAI) PADA MATA PELAJARAN AKUNTANSI PERBANKAN SYARIAH - Riris Ariska; Luqman Hakim (FKIP Unswagati, 2021)
AbstractThe learning paradigm in Indonesia continues to experience shifts to improve the quality and relevance of education. To realize the learning paradigm that currently applies, the government as a central institution seeks to perfect the curriculum. The current education curriculum in Indonesia is the 2013 curriculum. Learning in the 2013 curriculum uses a scientific approach to improve student activity and interactivity. Interactive multimedia based on Computer Assisted Instruction (CAI) one of the learning media that can increase the activeness and interactivity of students, so that learning becomes more effective and efficient. The drill and practice format on CAI is suitable for subjects that require an understanding of concepts and mastery of skills such as Syariah Banking Accounting. The purpose of this research is to analyze the development process, the feasibility, and the responses of students to interactive multimedia based on the Computer Assister Instruction (CAI) in Syariah Banking Accounting. This type of research is a research and development with the ADDIE development model of Reiser and Mollenda which consists of five stages including analysis, design, development, implementation, and evaluation. The results showed the average percentage obtained from the validation of material experts by 86,56% with the criteria “very feasible”, evaluation experts by 87,22% with the criteria “very feasible”, media experts by 93,52% with the criteria “very feasible”, and the response of students by 97,21% with the criteria “very good”. The overall results of the validation of the experts and the response of students obtained an average percentage of 91,13% so it can be concluded that the interactive multimedia that was developed is very feasible to use in learning and get a very good response from students.Keywords: interactive multimedia, Computer Assisted Instruction (CAI), Syariah Banking Accounting